Картографічні матеріали з фондів державного архіву Харківської області як джерело вивчення Слобідсько-Українського поселення кавалерії - Маршала, А. (Краєзнавство, 2016)
У статті досліджуються інформаційні можливості карт та топографічних планів населених пунктів та округів Слобідсько-Українського військового поселення кавалерії як історичного джерела, що дозволяє розглянути діяльність Межової Комісії, особливості будівельних процесів та територіальний устрій військових поселень в Слобідсько-Українській губернії. В статье исследуются информационные возможности карт и топографических планов населенных пунктов и округов Слободско-Украинского военного поселения кавалерии как исторического источника, который позволяет рассмотреть деятельность Межевой Комиссии, особенности строительных процессов и территориальное устройство военных поселений в Слободско-украинской губернии. The article explores the possibility of information maps and topographical plans of settlements and districts of the Slobodsko-Ukrainian military settlement of the cavalry, as a historical source. Consider the organization that engaged in inspection activities of the Slobodsko-Ukrainian military settlement of the cavalry and mapping, the authors of the individual plans are determined. The author examines the card approval process settlements, how was studying the formation of the territory of the districts of military settlements cavalry. Map study to determine the volumes of the building in different districts of the Slobodsko-Ukrainian military settlement of the cavalrytypes of buildings that are built , their location Particular attention is paid to the district of the Pskov Cuirassier Regiment. Based on the analysis of maps from the State Archives of Kharkiv regionstudied territorial of the Kharkov settlement. The article also examines the economic organization of the Slobodsko-Ukrainian military settlement of the cavalry.